Synthesis and antiproliferative activity of 2-aryl-4-(3, 4, 5-trimethoxybenzoyl)-1, 2, 3-triazol derivatives as microtubule-destabilizing agents. Issue 46 (5th June 2017) - Feng, Dongjie; Wu, Yue; Wang, Hao; Bai, Zhaoshi; Wang, Defa; Zuo, Daiying; Bao, Kai; Wu, Yingliang; Zhang, Weige
Abstract : A series of 2-aryl-4-(3, 4, 5-trimethoxybenzoyl)-1, 2, 3-triazols were designed as analogs of substituted methoxybenzoyl-aryl-thiazole (SMART) under the consideration of geometric features. Abstract : A series of 2-aryl-4-(3, 4, 5-trimethoxybenzoyl)-1, 2, 3-triazols were designed as analogs of substituted methoxybenzoyl-aryl-thiazole (SMART) under the consideration of geometric features. The target compounds were synthesized via concise and efficient processes including microwave-assisted cyclization, and were evaluated for their antiproliferative activity against three human cancer cell lines. Most compounds exhibited moderate antiproliferative activity with IC50 values in the micromolar to sub-micromolar range. Tubulin polymerization and immunofluorescence studies demonstrated that( Z )-9a was a potent microtubule-destabilizing agent and disrupted the polymerization dynamics. Moreover, ( Z )-9a significantly induced accumulation of cells in the G2/M phase and caused microtubule destabilization. Molecular modeling studies showed that( Z )-9a probably binds to the colchicine site of tubulin.